Variable Speed Drive DC-Bus Voltage Dip Proofing - Freeman Chiranga; Lesedi Masisi (Energies, 2021)
This paper proposes a power electronic module that uses a switched capacitor for retaining the integrity of the dc-link voltage of a variable speed drive (VSD) during a 0.2 s short-term power interruption (STPI). Ride-through was achieved through switched capacitor onto the dc bus. However, this technique presents a challenge of the high inrush currents during a ride through compensation. In this work both analytical and experimental investigations were conducted in order to reduce the in-rush currents and its impact on the performance of the VSD during the STPI. Inrush peak currents were reduced by approximately 90%. Experimental results showed torque pulsations of 12.8% and 14.3% at the start and end of dc-link voltage compensation, respectively. A method for sizing the switched capacitor and the inrush limiting resistors is proposed. This methodology is based on the use of readily available nameplate information of the VSD and the electric motor. The proposed module can be retrofitted to existing VSDs that are based on v/f control.